2016
DOI: 10.1099/mic.0.000345
|View full text |Cite
|
Sign up to set email alerts
|

Role of dihydrofolate reductase in tetrahydrobiopterin biosynthesis and lipid metabolism in the oleaginous fungus Mortierella alpina

Abstract: Mortierella alpina is a well-known polyunsaturated fatty acid-producing oleaginous fungus. Analysis of the Mort. alpina genome suggests that there is a putative dihydrofolate reductase (DHFR) gene playing a role in the salvage pathway of tetrahydrobiopterin (BH 4 ), which has never been explored in fungi before. DHFR is the sole source of tetrahydrofolate and plays a key role in maintaining BH 4 levels. Transcriptome data analysis revealed that DHFR was up-regulated by nitrogen exhaustion, when Mort. alpina st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The main functional component of FA is p -ABA [21]. Chen et al suggested that FA could promote lipid synthesis in microorganisms [12]. This may be the direct effect of p -ABA on lipid synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main functional component of FA is p -ABA [21]. Chen et al suggested that FA could promote lipid synthesis in microorganisms [12]. This may be the direct effect of p -ABA on lipid synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…S4B). The increase in the two enzymes accelerated the metabolism of the PPP, and the enhancement of tetrahydrofolate dehydrogenase and the PPP in the process was also observed, and more NADPH substrates could be provided [12]. In general, NADPH is the key substrate for lipid synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the genes involved in the phenylalanine hydroxylation system are absent in most fungal genomes [19], investigations of phenylalanine hydroxylation in the fungal kingdom have been lacking. Our laboratory is the first, to our knowledge, to sequence the whole genome of M. alpina [20] and comprehensively characterize the phenylalanine hydroxylation system in a fungus [3,19,21]. When M. alpina were cultured on a PAH inhibitor-containing medium, significant changes were observed in the lipid composition.…”
Section: Introductionmentioning
confidence: 99%
“…After sequencing the whole genome of M. alpina , we explored the presence of a putative MTHFDL gene in this fungus, which was first characterized in fungi in our laboratory [16, 17]. The inhibition of folate metabolism led to a decrease in the content of total fatty acid (TFA) and AA in M. alpina [18]. In addition, the differentiation of OP9 bone marrow stromal cells into fat cells was inhibited by the inhibition of folate metabolism [19].…”
Section: Introductionmentioning
confidence: 99%